Fractional soliton dynamics of electrical microtubule transmission line model with local M-derivative - Raza, Nauman; Arshed, Saima; Khan, Kashif Ali; İnç, Mustafa (Iop Publishing Ltd, 2021)
In this paper, two integrating strategies namely exp[-phi(chi)] G'/G(2)-expansion methods together with the attributes of local-M derivatives have been acknowledged on the electrical microtubule (MT) model to retrieve soliton solutions. The said model performs a significant role in illustrating the waves propagation in nonlinear systems. MTs are also highly productive in signaling, cell motility, and intracellular transport. The proposed algorithms yielded solutions of bright, dark, singular, and combo fractional soliton type. The significance of the fractional parameters of the fetched results is explained and presented vividly.
Keywords: solitons solution; microtubule; nonlinear transmission line; {G '/G(2))-expansion method